Electrical Transport Characteristics and Deep Level Transient Spectroscopy of Ni/V/n-InP Schottky Barrier Diodes - V.Rajagopal Reddy; S.Sankar Naik (Журнал нано- та електронної фізики)
We report on the temperature-dependent electrical characteristics and deep level transient spectroscopy (DLTS) of the Ni/V/n-InP Schottky diodes in the temperature range of 180-420 K. Current density - voltage (J-V) characteristics of these diodes have been analyzed on the basis of thermionic emission theory with Gaussian distribution model of barrier height. The calculated Schottky barrier height (bo) and ideality factor (n) of Ni/V Schottky contact is in the range of 0.39 eV and 2.36 at 180 K, and 0.69 eV and 1.27 at 420 K, respectively. It is observed that the zero-bias barrier height increases while ideality factor decreases with increasing temperature. A bo versus q/2kT plot is drawn to obtain evidence of a Gaussian distribution of the barrier heights, and values of  = 0.95 eV and 0 = 128 eV for the mean barrier height and standard deviation. A modified Richardson plot gives (T=0)= 0.98 eV and Richardson constant (A*) = 7.068 A K – 2cm – 2. The discrepancy between Schottky barrier height (SBHs) estimated from J-V and C-V measurements is also discussed. Thus, it is concluded that the temperature dependence of J-V characteristics of the SBHs on n-InP can be explained on the basis of themionic emission mechanism with Gaussian distribution of the barrier heights. DLTS results showed that two deep levels are identified (E1 and E2) in as-grown sample having activation energies of 0.29 ± 0.01 and 0.69 ± 0.02 with capture cross-section 3.29 × 10 – 15 cm2 and 5.85 × 10 – 17 cm2 respectively.